A new species of the snake genus Amphiesma (Serpentes: Colubridae: Natricinae) from western Sumatra, Indonesia - David, Patrick; Das, I. (National University of Singapore, 2003)
A new species of the natricine genus Amphiesma is described from the slopes of Gunung Kerinci, western Sumatra, Indonesia. Amphiesma kerinciense is distinguished from other species of the Sunda Region, namely West Malaysia, Sumatra and Borneo, by a combination of morphological characters. Its relationships, especially with Amphiesma sanguineum , are discussed, and a key to the Amphiesma species of the Sunda Region is provided